ANALISIS PROSES PEMECAHAN MASALAH PESERTA DIDIK DALAM MENYELESAIKAN SOAL BERORIENTASI PISA - Marlinda Indah Eka Budiarti; Faida Musa’ad; Supriadi Supriadi (Program Studi PGSD Universitas Flores, 2023)
Based on the results of PISA data since 2000 in the last 7 periods, Indonesia is still ranked low, while if you refer to the objectives of education to produce students who have the ability to think critically, and reason so that they have the ability of Higher Order Thinking Skill (HOTS). So it is hoped that students can often practice working on PISA-oriented questions, resulting in an increase in the level of Indonesian students to a higher level. The purpose of this study was to describe the problem-solving process of students in solving PISA-oriented problems. The subjects used in this study were three VIII-grade students at MTs Algebra Sorong, with qualitative methods. The research approach used descriptive qualitative, with data collection techniques using test results and interviews. The results of this study are at the stage of understanding the problem, students often fail to understand because they are in a hurry or because of the rarity of PISA questions used for problem practice at school. While at the stage of making a problem-solving plan, students neglect to write it in the answer sheet because they are in a hurry. Then at the stage of implementing the plan, students still have miscalculations due to calculation errors. At the stage of looking back at the results obtained, students often consider it unimportant or are written casually.